Exploration of predictive markers associated with primary angle-closure glaucoma risk in companion dogs using genomic information - Ji Hyun Jun; Gwang Hyeon Lee; Zultsetseg Byambasuren; Hong Sik Kong (Journal of Animal Reproduction and Biotechnology)
Background: With the growing interest in the health of companion dogs, their average lifespan has increased, leading to an increase in the proportion of elderly dogs. As elderly dogs are vulnerable to various diseases, there is a need for alternatives to predict the risk of major diseases in senior dogs, prevent them in advance, and manage their health effectively. Therefore, this study was conducted to identify candidate genes and single nucleotide polymorphisms (SNPs) influencing primary angle-closure glaucoma, a major disease in elderly dogs, using the Axiom Canine HD Array and establishing foundational data. Methods: Samples from 95 dogs of 26 breeds from South Korea were analyzed using an SNP chip. Ultimately, two SNPs were selected. To assess the impact of non-synonymous SNP (nsSNPs), functional analysis of candidate genes, Hazard Assessment, and protein structure prediction were conducted. Sequencing for SNP validation involved samples from 95 dogs of ten breeds with reported domestic and international glaucoma cases. Results: The candidate gene TNS1 was associated with the integrin signaling pathway. The selected nsSNP was found to cause a mutation at the ninth position of the amino acid sequence, changing serine to leucine and resulting in alterations to the overall protein structure. Sequencing analysis results for SNP validation revealed differences in frequency among breeds. Conclusions: The identified SNP markers are potential risk prediction tools. Utilizing genotype frequency data by breed and individual could aid in disease management and contribute to advancements in the medical industry.